Diseño conceptual de cascadas de enriquecimiento de uranio. - Acosta, Gonzalo M. (Comisión Nacional de Energía Atómica. Instituto Balseiro, 2011)
Fil. Acosta, Gonzalo M.. Comisión Nacional de Energía Atómica. Instituto Balseiro; Argentina